Influence of image reconstruction protocols on the image quality of a small animal PET scanner using 18F and 11C - João Vitor do Carmo Barbosa; Rodrigo Modesto Gadelha Gontijo; Guilherme Cavalcante de Albuquerque Souza; Bruno Melo Mendes; Juliana Batista da Silva; Marcelo Mamede; Andréa Vidal Ferreira (Brazilian Journal of Radiation Sciences, 2021)
The small animal positron emission tomography (PET) scanner from Molecular Imaging Laboratory (LIM/CDTN) is dedicated to pre-clinical studies on new 18F and 11C-based radiopharmaceuticals and to development of novel applications for well-known radiopharmaceuticals. Thus, quality control tests recommended by the publication NEMA NU 4-2008 are routinely carried out to ensure the proper performance of PET scanner. The aim of this work was to evaluate the influence of image reconstruction protocols on the image quality, accuracy of attenuation and scatter corrections parameters for 18F and 11C PET images. PET images of the image quality phantom filed with 18F-FDG or 11C-PK1122 were acquired and then reconstructed using different reconstruction protocols. The reconstruction variables evaluated were the algorithms (FBP, MLEM-3D, OSEM-3D), the resolution mode (high/standard) and the number of iterations (10 to 150). Uniformity, spill-over ratio (SOR) and recovery coefficients (RC) tests were performed for each reconstructed image according NEMA NU 4-2008. PMOD software was used for image analysis. FBP based protocol generated noisier images compared to iterative algorithms (MLEM-3D or OSEM-3D) based protocols. The increase in the number of iterations resulted in higher standard deviation of the analyzed parameters for all reconstructed images. MLEM-3D and OSEM-3D based protocols generates similar results when number of iterations and resolution mode were identical. SOR and RC mean values remained stable when the number of iterations ranged from 40 to 150. This study allowed the evaluation of different image reconstruction protocols on important parameters of 18F and 11C PET image quality. Additionally, standard image reconstruction protocols to be adopted in LIM/CDTN laboratorial routine for 18F and 11C images reconstruction in preclinical studies were defined.